Impact of educational intervention on breastfeeding practices of mother undergoing institutional delivery - Rai, Rajesh; Khatun, Reshma; Inamdar, Prithi; Patil, Rohan (International Journal of Contemporary Pediatrics, 2023)
Background: Existing literature shows that education and supportive interventions, both for breast-feeding mothers as well as for healthcare professionals, can increase the proportion of women that use exclusive breast-feeding. Healthy nursing practise can be encouraged by offering mothers the proper guidance from medical professionals and by designing educational programmes that explicitly target women with low levels of education and few resources. Aims was to study the effect of structured educational intervention for improving appropriate breastfeeding practices at 6-8 weeks of birth and to evaluate the factors causing deviation from recommended breastfeeding norms. Methods: An interventional study was done to assess breastfeeding knowledge, attitude and practices of mother undergoing institutional delivery in the Department of Paediatrics, D. Y. Patil University School of Medicine, Nerul, Navi Mumbai. Continuous Data was presented as mean, median, and standard deviation. Categorical data were presented as frequency and percentages. Statistical analysis was carried out with the help of statistical test such as Chi-square test to know the significant relationship and software used was SPSS 26. The level of significance was set at 5%. All p values less than 0.05 was treated as significant. Results: We found that additional educational intervention over and above to routine counselling significantly improved knowledge of not using pre-lacteal feeds in intervention group (p=0.0003), the understanding of importance of colostrum (p=0.001). Most importantly, Group 1 had exclusive breastfeeding rate of 74.5% (149/200) as compared to group 2 with additional intervention; who had exclusive breastfeeding rate of 93.5% (187/200) (p<0.0001). Conclusions: We could conclude that educational interventions in a structured format in the postnatal period can increase the exclusive breastfeeding rates and sustain it further lowering the mortality significantly.